2015
DOI: 10.5301/tj.5000378
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Primary Endometrial and Ovarian Cancers: A Multicenter Review of 63 Cases

Abstract: Our study demonstrated that optimal cytoreduction, early-stage disease, and LVSI are the most significant factors affecting survival in women with SEOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…We can say that these findings are similar to the literature [1,9,28,34,40,41]. The 5-year PFS of SOEC patients is around 65% [28][29][30]. The 5-year overall survival is between 73-86% [30,39].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We can say that these findings are similar to the literature [1,9,28,34,40,41]. The 5-year PFS of SOEC patients is around 65% [28][29][30]. The 5-year overall survival is between 73-86% [30,39].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, among the patients operated for epithelial ovarian cancer, 36 patients were diagnosed with synchronous primary endometrial cancer and our rate was found to be 8.8% (36/409). When the literature is reviewed, the number of patients in most studies on this subject does not exceed 100 [7,[28][29][30]. At the same time, the correct recognition of this clinical condition is extremely important as it affects the adjuvant treatment and survival, because some SOEC patients are mistakenly diagnosed with stage 2A ovarian cancer or stage 3A endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The current FIGO system assigns these patients as stage IIIA, which triggers adjuvant management by chemotherapy and radiotherapy in the European Society of Gynecologic Oncology and National Comprehensive Cancer Network treatment guidelines (1,2). This management approach may be overtreatment for a subset of such patients who have long been recognized to follow a favorable outcome that more closely aligns with patients whose disease is confined to the uterus (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). This suggests that such patients are better served by being distinguished from the typical stage IIIA population and managed by less aggressive adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of synchronous primary endometrial and ovarian cancers in gynecological tumors is only 0.7%-1.8% [4]. They are clinically difficult to distinguish and often misdiagnosed for the metastasis of endometrial cancer to the ovary or ovarian cancer to the uterus.…”
Section: Discussionmentioning
confidence: 99%